Superfícies de curvatura média constante um no espaço hiperbólico - Santos, Márcio Silva (2011)
In this work the crucial point is to obtain a holomorphic representation for mean curvature one surfaces in hyperbolic space. This representation has a great resemblance to the Weierstrass representation for minimal surfaces in R3: From this, we obtain a range of results about the theory of mean curvature one surfaces complete and finite total curvature in H3.